Direct Continuous Method for Monitoring Biofilm Infection in a Mouse Model - Kadurugamuwa, Jagath L. (American Society for Microbiology, 2003)
We have developed a rapid, continuous method for real-time monitoring of biofilms, both in vitro and in a mouse infection model, through noninvasive imaging of bioluminescent bacteria colonized on Teflon catheters. Two important biofilm-forming bacterial pathogens, Staphylococcus aureus and Pseudomonas aeruginosa, were made bioluminescent by insertion of a complete lux operon. These bacteria produced significant bioluminescent signals for both in vitro studies and the development of an in vivo model, allowing effective real-time assessment of the physiological state of the biofilms. In vitro viable counts and light output were parallel and highly correlated (S. aureus r = 0.98; P. aeruginosa r = 0.99) and could be maintained for 10 days or longer, provided that growth medium was replenished every 12 h. In the murine model, subcutaneous implantation of the catheters (precolonized or postimplant infected) was well tolerated. An infecting dose of 10 (3) to 10 (5) CFU/catheter for S. aureus and P. aeruginosa resulted in a reproducible, localized infection surrounding the catheter that persisted until the termination of the experiment on day 20. Recovery of the bacteria from the catheters of infected animals showed that the bioluminescent signal corresponded to the CFU and that the lux constructs were highly stable even after many days in vivo. Since the metabolic activity of viable cells could be detected directly on the support matrix, nondestructively, and noninvasively, this method is especially appealing for the study of chronic biofilm infections and drug efficacy studies in vivo.